The Other Darwin’s Plots: Evolution as Literature in Erasmus Darwin, Samuel Butler and George Bernard Shaw - Priestman, Martin (Romanticism and Victorianism on the Net, 2016)
Whereas Gillian Beer’s Darwin’s Plots traces the sometimes-indirect impact of Charles Darwin on a number of major Victorian novels, this article proposes to examine the fictions of two writers very directly concerned with evolution, but preferring what they took to be Erasmus Darwin’s version of it. The first of these is Samuel Butler, who progressed from sympathetically spoofing Charles’ evolutionism to bitterly attacking his theory of natural selection, holding up what he believed to be the goal-directed evolutionary model of Erasmus and others instead. Along with a glance at Butler’s polemical evolutionary works, his two major novels Erewhon and The Way of All Flesh are explored both for their critiques of Charles and the ways they may have drawn on Erasmus, particularly his Botanic Garden and Zoonomia.The other writer with links to Erasmus is George Bernard Shaw, the Preface to whose ambitious five-play cycle Back to Methuselah denounces Charles and explicitly praises both Butler and Erasmus’s Zoonomia, while its plot bears interesting similarities to Erasmus’s final evolutionary poem, The Temple of Nature. Since it is not certain Shaw had read this poem the following comparison runs the unproved possibility of direct influence in parallel with Viktor Shklovsky’s idea of the transmission of literary forms in a series of “knight’s moves,” “discontinuous but teleological” as Fredric Jameson calls them. While the parallels between the two works are striking, including the political contexts to which they are responding, the article finally distances Erasmus’s full-blooded but non-exclusory evolutionism from the hints of “survival of the fittest” Social-Darwinism to be found in Shaw’s (and to a lesser extent Butler’s) works.